In vitro effect of uremic serum on barrier function and inflammation in human colonocytes - Andrade,Laila Santos de (2018)
ABSTRACT Introduction: In chronic kidney disease (CKD), it has been suggested that alterations within the gut are associated with an inflammatory state and uremic toxicity. Studies suggest that uremia may impair the function of the intestinal barrier via the promotion of increased intestinal permeability. To understand the mechanisms that are involved in intestinal barrier damage in the setting of uremia, we evaluated the in vitro effect of uremic serum on transepithelial electrical resistance (TER), inflammation, and apoptosis in intestinal epithelial cells (T84). Methods: Pools of serum from healthy individuals, patients not on dialysis, and patients on hemodialysis (Pre-HD and Post-HD) were prepared. T84 cells were incubated for 24 h in medium, of which 10% consisted of the pooled serum from each group. After incubation, the TER was measured and the following parameters were determined by flow cytometry: expression of toll-like receptors (TLRs), production of reactive oxygen species (ROS), and apoptosis. The level of IL-6 in the culture supernatant was determined by ELISA. Results: No difference was observed among the groups with respect to TER, apoptosis, and ROS or the expression of TLR-2, TLR-4, and TLR-9. IL-6 secretion was higher (p < 0.001) in cells that were incubated with pre- and post-HD serum. Conclusion: The results that were obtained from this model suggest that uremic serum per se does not seem to impair the integrity of intestinal epithelial cells. The increased IL-6 secretion by cells that were incubated with HD serum suggests a potential effect of uremia in the intestinal inflammatory response.